ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYERAPAN ANGGARAN PADA PEMERINTAH DAERAH KABUPATEN BATANG - Hasni, Nanik Tsania; Basukianto, Basukianto (Jurnal Ilmiah Telaah Manajemen, 2016)
The purpose of this research is to analyze and describe the influence and activities of budget planning, procurement, human resource competencies, regulations and disbursement process to absorption in Batang regency government. The population in this research were employees of 52 regional work units(SKPD)and 8 officers at the District Secretariat at Batang Regency. The sample used officials related to the disbursement of the budget namely the Financial Administration Officer (PPK) SKPD, treasurer and treasurer expenditure at Batang regency government. Data in this research is the primary data sourced from the questionnaire. Analysis techniques data using SPSS regression program. The results of this research can be concluded that the budget and activity planning, procurement, human resource competencies, regulations and the disbursement process positively affects to the uptake budgetThe most dominant to influence the uptake budget followed by a variable the planning and activities , the disbursement process of funds, procurement of goods and services and human resource Keywords: budget planning and activities, procurement, human resource competencies, regulations and disbursement process and the absorption of budget